Electronic Structure of Vanadium-Doped TiO2 of Both Anatase and Rutile Based on Density Functional Theory (DFT) Approach - Hari Sutrisno (ALCHEMY Jurnal Penelitian Kimia, 2018)
Study of the theoretical  approah to calculate the band structure and density of states (DOS) of vanadium-doped TiO2 of both anatase and rutile have been done. The first-principle calculations were done using supercell (2x1x1) method. The first-principle calculation of V-doped TiO2 of both anatase and rutile were analyzed by density-functional theory (DFT) with generalized gradient approximation from Perdew-Burke-Ernzerhof (GGA+PBE), Perdew-Wang’s 1991 (GGA+PW91) and local density approximation (LDA) for exchange-correlation functionals. The calculation of electronic structures show that the V-doped TiO2-anatase with high concentration (7.93%) in 24 atoms are direct- and indirect-gap semiconductor, whereas the V-doped TiO2-rutile with high concentration (15.79%) in 12 atoms is direct-gap semiconductor. The V-doped TiO2 of both anatase and rutile produce the intermediate bands in the upper states. Ihe V-doped anatase produces intermediate band, which is 2.05, 2.04, 2.06 eV above the valence band for GGA+PBE, GGA+PW91 and LDA, respectively. Meanwhile the V-doped rutile producesintermediate band, which is 1.76, 1.82, 1.74 eV above the valence band for GGA+PBE, GGA+PW91 and LDA, respectively.